Dietary intake and nutrient adequacies among women of reproductive age in northern Tanzania: A cross-sectional study - Azupogo, Fusta; Arnold, Charles D.; Bliznashka, Lilia; Makori, Nyabasi; Njau, Calista N.; Malindisa, Evangelista; Jeremiah, Kidola; Kinabo, Joyce; Olney, Deanna K.; Hess, Sonja Y. (Elsevier, 2026)
Background Dietary inadequacies among women of reproductive age (WRA) increase malnutrition and disease risk.